Constrained codes in single-reader/two-track reading bit-patterned magnetic recording - Siwakon Sokjabok; Mutita Mattayakan; Chaiwat Buajong; Santi Koonkarnkhai; Piya Kovintavewat; Chanon Warisarn (AIP Advances, 2021)
A reduction in track width of ultra-high density magnetic recording such as bit-patterned media recording (BPMR) results in an increase in areal density. However, the unfortunate appearance of extreme inter-symbol interference (ISI) and inter-track interference (ITI) can severely deteriorate the system performance. To deal with these problems, we propose to use a single-reader/two-track reading (SRTR) technique, where a single reader was employed to read two parallel-track at once and the bit islands were arranged in a staggered manner. Then, a received readback signal was sampled at an over-sampling rate, where an obtained data sequence can be operated using only a one-dimensional equalization and detection scheme. Moreover, we also present the simple constrained coding schemes consisting of the rate-3/5 and -4/6 constrained codes, where both are properly designed for an SRTR BPMR system by avoiding all data patterns that are more susceptible to ISI and ITI effects. Simulation results show that the severe ISI and ITI effects can be mitigated through the use of our proposed coding schemes. Consequently, the proposed systems are superior to the conventional system (without our constrained codes) at a same user density of 3.0 Tb/in2.
Keywords: Magnetic properties of thin films; Cellular Automata and Applications; Advanced Data Storage Technologies